2015
DOI: 10.1039/c4ra16006a
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional colloidal crystal heterostructures

Abstract: A simple method to fabricate colloidal crystal heterostructures based on a two-dimensional colloidal crystal was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Advances aimed at multifunctional materials for photonic healthcare devices have been made for portable healthcare and personalized medicines. For 2D CPC devices, modifications in optical fibers, heterostructures, and molecular imprinting sensors were reported with enhanced properties, which might have enhanced glucose-sensing properties as emerging devices [94][95][96][97]. For 3D CPC systems, the test paper-like CPC materials provide rapid chemical separation and visual response as potential devices in glucose detection [98,99].…”
Section: Other Emerging Devicesmentioning
confidence: 99%
“…Advances aimed at multifunctional materials for photonic healthcare devices have been made for portable healthcare and personalized medicines. For 2D CPC devices, modifications in optical fibers, heterostructures, and molecular imprinting sensors were reported with enhanced properties, which might have enhanced glucose-sensing properties as emerging devices [94][95][96][97]. For 3D CPC systems, the test paper-like CPC materials provide rapid chemical separation and visual response as potential devices in glucose detection [98,99].…”
Section: Other Emerging Devicesmentioning
confidence: 99%
“…These PS monolayers were successfully applied for visual detection applications after embedding it into a sensitive chitosan hydrogel. Xue and co‐workers reported the fabrication of 2D colloidal monolayer arrays of Poly ( methyl methacrylate) (PMMA) particle by using the self‐assembly method at the air‐water interface . Gao and co‐workers reported the fabrication of a large‐scale PS monolayer with ultra‐high throughput at the air‐water interface by using a micropropulsive injection (MPI) method .…”
Section: Self‐assembly Of Nanoparticle At the Air‐liquid Interfacementioning
confidence: 99%
“…Xue and co-workers reported the fabrication of 2D colloidal monolayer arrays of Poly ( methyl methacrylate) (PMMA) particle by using the self-assembly method at the air-water interface. [45] Gao and co-workers reported the fabrication of a large-scale PS monolayer with ultra-high throughput at the air-water interface by using a micropropulsive injection (MPI) method. [44] Figure 3H presents the MPI systems, and Figure 3I illustrates the dynamic and equilibrium state near the interface between the tip of the injector and surface of the water.…”
Section: Self-assembly Of Organic Nanoparticlesmentioning
confidence: 99%
“…Compared to 3D-PC, 2D-PC could not only realize the selfassembly preparation in just several minutes, but could also form a Debye diffraction ring under the illumination of a commercial laser pointer, which can be easily applied to quantify the variation of analyte concentration. 28,29 However, until now, only a few studies have been reported about the detection of organophosphates via 2D-PC.…”
Section: Introductionmentioning
confidence: 99%